Edison's alley - Shusterman, Neal; Elfman, Eric (2015)
"Nick and his friends race against their foes to retrieve more pieces of Tesla's free energy transmitter, only to see them fall into the hands of the Accelerati's shadowy leader"--
Keywords: Tesla, Nikola, -- 1856-1943 -- Fiction; Inventions -- Fiction; Science fiction; Colorado Springs (Colo.) -- Fiction